Minimum wage increases and vacancies - Marianna Kudlyak; Murat Tasci; Didem Tüzemen (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
Using a unique data set and a novel identification strategy, we estimate the effect of minimum wage increases on job vacancy postings. Utilizing occupation-specific countylevel vacancy data from the Conference Board's Help Wanted Online for 2005-2018, we find that state-level minimum wage increases lead to substantial declines in existing and new vacancy postings in occupations with a larger share of workers who earn close to the prevailing minimum wage. We estimate that a 10 percent increase in the statelevel effective minimum wage reduces vacancies by 2.4 percent in the same quarter, and the cumulative effect is as large as 4.5 percent a year later. The negative effect on vacancies is more pronounced for occupations where workers typically have lower educational attainment (high school or less) and in counties with higher poverty rates. We argue that our focus on vacancies versus on employment has a distinct advantage of highlighting a mechanism through which minimum wage hikes affect labor demand. Our finding of a negative effect on vacancies is not inconsistent with the wide range of findings in the literature about the effect of minimum wage changes on employment, which is driven by changes in both hiring and separation margins.
Keywords: E24; E32; J30; J41; J63; J64; 330; Minimum Wage; Vacancies; Hiring; Search and Matching